Exploring Personality Traits, Coping Strategies, and 5-Year Change in Blood Pressure in Young Adults: The African-PREDICT Study - Anchenique Papenfus; Karel Botha; Carina Mels; Marike Cockeran (SAGE Publishing, 2024)
This sub-study of the African Prospective Study on the Early Detection and Identification of Cardiovascular Disease and Hypertension (African-PREDICT) explored possible early psychological predictors of change in blood pressure. In a sample of normotensive at baseline black and white South Africans ( n  = 105; mean age at baseline 24.93), this study investigated the relationship between personality traits, coping strategies, and 24-hour ambulatory blood pressure measured at baseline and 5-year follow-up. Another aim was to investigate a possible mediating effect of coping strategies on the relationship between personality traits and change in blood pressure. Extraversion, agreeableness, openness, and problem-solving skills were identified as possible protective factors against cardiovascular risk, confirming previous research in this regard. However, the effect of these was different for gender and ethnic subgroups. Preconditions for a possible mediation role for coping in the relationship between personality and change in blood pressure were not met. Future research should further explore gender and ethnic differences in the relationship between personality, coping, and cardiovascular health.